Known and novel parvoviruses identified in domestic pigeons - Ewa Łukaszuk; Daria Dziewulska; Anthony Khalifeh; Joy M. Custer; Simona Kraberger; Arvind Varsani; Tomasz Stenzel (BMC Veterinary Research)
Abstract Background Parvoviridae is a family of single-stranded linear DNA viruses whose members infect both vertebrate and invertebrate species of animals, causing diseases of various systems and often associated with pathology of the gastrointestinal tract. Additionally, parvoviruses are known to induce illnesses causing diarrhea in various avian species as well; however, data on their occurrence and pathology in pigeons is scarce. Results In this study, we developed molecular biology methods to detect and quantify parvovirus genetic material in samples acquired from racing pigeons of different health status. Our intention was to determine a connection between the presence of the virus and the occurrence of clinical signs in sampled birds. The results of quantitative analysis indicate no direct association of parvoviruses with the manifestation of enteric disease in pigeons. High-throughput sequencing was performed on samples testing positive in quantitative PCR with TaqMan probe and in digital droplet PCR. It allowed us to assemble two coding-complete pigeon parvovirus genomes, one belonging to new species and referred to as pigeon parvovirus 2, and the second which is a member of species Aveparvovirus columbid1. Additionally, we analyze two coding-complete genomic sequences acquired from pigeon feces in USA, one representing species Aveparvovirus columbid1 and one being a member of Chaphamaparvovirus genus in Hamaparvovirinae subfamily. Conclusions This is the first report of parvovirus in pigeons outside Asia. The findings of our research emphasize the need to further explore the poorly understood biology and pathology of pigeon parvoviruses.